565 UNUSUAL LIFE-THREATENING FLECAINIDE TOXICITY: A CASE REPORT. (15th December 2022) - Strangio, Antonio; Caracciolo, Alessandro; Rizzuti, Guglielmo; Leo, Isabella; Quero, Michele; Sulla, Antonio; Megna, Fabio
Abstract: Background: Anti-arrhythmic drug therapy has often a narrow therapeutic index and could be responsible of toxic side effects including malignant arrhythmias and life-threatening hemodynamic deterioration. Flecainide toxicity can occur even at normal serum levels in the setting of electrolyte disturbances such as hyponatremia. We report a case of flecainide toxicity, likely due to dual mechanism: reduced excretion and potentiation of the toxic effects due to concomitant hyponatremia. Case description: A 82-year-old woman was admitted to our hospital for syncope. The ECG at admission showed atrial fibrillation, complete atrio-ventricular (AV) block and a wide QRS escape rhythm. She has a history of hypertension, COPD and atrial fibrillation. She was currently taking flecainide at a dosage of 150 mg per die. Laboratory tests reported an elevated lactate concentration (4.6 mmol/L), hyponatremia (128 mmol/L), severe reduction of renal function (eGFR 19 ml/min), and NT-proB-type Natriuretic Peptide 17563 pg/ml, (ULN<450). Echocardiography showed a reduced left ventricular ejection fraction (EF=35%). Suspecting flecainide poisoning, we started intravenous sodium bicarbonate and temporary pacing for severe bradycardia and pauses. However, despite numerous attempts of lead reposition and the use of maximum output, we failed to document ventricular capture in the immediate post-operative. Half hour later, dopamine infusion was started for sustained severe hypotension. The day after we were able to obtain ventricular capture. At serial ECG examination, she also developed progressive QRS narrowing with concomitant clinical improvement. Discussion: Flecainide toxicity is a rare but potentially life-threatening condition. The excess of sodium channel blockade causes in fact delayed conduction through the AV node, His-Purkinje system, and ventricles with possible AV block, ventricular tachycardia, ventricular fibrillation, and asystole. In addition, hemodynamic instability can develop rapidly in flecainide intoxication due to chronotropic and inotropic incompetence. The majority of flecainide intoxication reported cases are due to a drug overdose. However, flecainide toxicity can occur with serum levels within the range of normality. Particularly, this can occur in the setting of hyponatremia. The observed pacemaker malfunction was also due to flecainide intoxication. In our case, the patient was taking therapeutic doses of this drug. The toxic effect was probably due to the reduced excretion (secondary to kidney failure) and the simultaneous presence of hyponatremia. The main treatment for flecainide intoxication is sodium bicarbonate and supportive care. However, there is currently no recommended standardized protocol for flecainide toxicity. The inotropic agents could be helpful in case of cardiogenic shock, but their use may be limited by the rate-dependent effect of flecainide and the increased risk ventricular arrhythmias. Left ventricular assist devices have been also used to support hemodynamic through flecainide-induced cardiogenic shock.